Software Engineering and eLearning: The MuSofT Project - www.musoft.org - Ernst-Erich Doberkat; Gregor Engels; Jan Hendrik Hausmann; Marc Lohmann; Jörg Pleumann; Jens Schröder (FernUniversität Hagen, 2005)
eLearning supports the education in certain disciplines. Here, we report about novel eLearning concepts, techniques, and tools to support education in Software Engineering, a subdiscipline of computer science. We call this "Software Engineering eLearning". On the other side, software support is a substantial prerequisite for eLearning in any discipline. Thus, Software Engineering techniques have to be applied to develop and maintain those software systems. We call this "eLearning Software Engineering". Both aspects have been investigated in a large joint, BMBF-funded research project, termed MuSofT (Multimedia in Software Engineering). The main results are summarized in this paper.